The Academic Demoralization of Students in Online Learning During the COVID-19 Pandemic - Muassomah, Muassomah; Abdullah, Irwan; Hasanah, Umdatul; Dalmeri, Dalmeri; Sihombing, Adison Adrianus; Rodrigo, Luis (Frontiers in Education, 2022)
Academic moralization, which has been internalized through educational institutions with teacher supervision at schools, now falls into a decline, in line with the implementation of distance education due to the Covid-19 pandemic. This paper aims to show that an educational system, which does not present teachers in the real life, leads students to ignore the values of academic morality, such as plagiarism, discipline, and responsibility. This paper employs a qualitative descriptive method by relying on online news mapping data as a secondary source, and verified by data from interviews with elementary school students as the primary source. The results of this study indicate that online education as a learning solution during the pandemic has caused students to plagiarize, to cheat, to rely their task on others, and to lose discipline and sense of responsibility. This study suggests a new direction of moral education that does not only rely on teacher supervision, but rather builds the wisdom of students' independence upon learning.